Social Skills in Elementary Students: The Role of Attitude to School and School Environment - Marjan Kian; Zeynab Adibnasab; Balal Izanloo (Shiraz University of Medical Sciences, 2020)
Background: Formation of social skills in elementary students is usually dependent on several factors, which need to be identified for the improvement of school outputs. The purpose of this study was to predict social skills of students based on attitude towards school and school environment. Methods: A descriptive-correlational method was used. The statistical population consisted of all high school female students in Qazvin in the academic year 2018-2019. Using cluster sampling, 240 students were selected as the sample. The tools included Delaware School Climate, Gresham and Elliot's Social Skills, and McCook and Siegel's Attitude to School questionnaires. To analyze the data, some descriptive and inferential statistics were used for multivariate analysis of variance and structural equation modeling. Results: The findings showed that "responsibility" (22.03), "attitude toward teacher and class" (35.42), and "student-teacher relations" (21.35) had the highest mean in public schools. Furthermore, in non-public schools, "responsibility" (22.24), "motivation/self-regulation" (51.90) and "student-teacher relations" (25.15) had the highest mean. In addition, there was a positive correlation between some "school climate" dimensions and "attitude to school" and "social skills", by P=0.001 (cooperation=0.023, assertiveness=0.012, accountability=0.0001, participation=0.020, self-control=0.024). The highest effect belonged to "cooperation" and "responsibility", and the lowest effect pertained to "sympathy". There was no significant difference between public and non-public schools regarding "communication" (P=0.021) and "cooperation" (P=0.0154). Moreover, "school environment" was different in school type (P=0.001), but "attitude to school" did not differ significantly (P>0.05). Conclusions: Based on the results, it could be said that the association between school environment and attitude to school can be an important factor in dealing with social skills; therefore, to improve students' social skills, it is recommended that the educational planners pay more attention to the quality of schools' environment and attitude to school.